Rosalía de Castro and the problem of self-translation - do Cebreiro Rábade Villar, María (Madrygal. Revista de Estudios Gallegos, 2011)
Taking as a starting point the comparison of some narrative fragments and poems of Rosalía de Castro, this article explores the continuity between her literary production in Galician and her literary production in Castilian. This continuity is placed in the context of practices of self- translation. The aim is to examine the implications of the bilingual character of the author’s work from a critical perspective.
Keywords: Rosalía de Castro; self-translation; transduction; literary bilingualism; Follas Novas; Flavio; Cantares gallegos; black shadow.